TECHNOLOGY-ENABLED HEROINE: AN ANALYSIS ON WOMAN CYBORG IN ALITA: BATTLE ANGEL FILM - Salsabila, Wahdah Kamelia; Cahyo, Pujo Sakti Nur (PARADIGM: Journal of Language and Literary Studies, 2024)
This study closely examines the character of Alita in the film Alita: Battle Angel to determine whether she represents women’s empowerment. Heroines are often portrayed as powerful and independent figures who challenge traditional gender roles. To analyze Alita's character, this study utilizes Greimas' actantial model of narrative structure and Donna Haraway’s concept of the cyborg from A Cyborg Manifesto. Greimas' model helps dissect the narrative roles and relationships, while Haraway's concept aids in understanding the intersection of technology and gender. The analysis reveals that Alita embodies certain elements of women’s empowerment. She displays physical strength, resilience, and a sense of autonomy that are typically associated with empowered female characters. Alita's journey of self-discovery and her fight against oppressive forces resonate with themes of independence and empowerment. However, a deeper examination of the film's narrative structure and character dynamics uncovers underlying patriarchal elements. Despite Alita's strengths, the film presents a technological hierarchy where male characters, particularly Dr. Dyson Ido and Vector, hold significant control and influence over Alita and other female characters. This dynamic suggests that while Alita is portrayed as a powerful figure, her agency is still constrained within a male-dominated technological framework. Furthermore, the film's depiction of Alita as a cyborg complicates the narrative of empowerment. Haraway's cyborg theory suggests that cyborgs can transcend traditional gender boundaries and challenge patriarchal structures. Yet, in Alita: Battle Angel, the cyborg nature of Alita is used to emphasize her otherness and dependence on male characters for her identity and purpose. This reinforces traditional gender hierarchies rather than subverting them.